Daftar Jenis Vertebrata Darat di Pembangkit Listrik Tenaga Air (PLTA) Besai - Tohir, Rizki Kurnia; Hasibuan, Mhd Muhajir; Anita, Vilda Puji Dini; Lubis, Arie Mulia; Fatara, Fadhel; Setyawan, Ari; Azhaar, Daliilah Haniifah; Christoper, Ruben; Johanes, Ricky; Pandapotan, Sumitro; Aziz, Agung Abdul (Wana Lestari, 2025)
Hydropower plants are often considered a negative factor affecting biodiversity conservation; however, some studies have noted that they can also serve as biodiversity refugia from the pressures of forest cover change in the surrounding areas. This study aimed to identify the biodiversity within the Besai Hydropower Plant (PLTA Besai) concession area. Data collection was performed using several methods, including strip transects, trapping, and track detection for mammals; a point count combined with transects for birds; and visual encounter surveys for amphibians and reptiles. The results recorded the presence of 88 terrestrial vertebrate species, comprising 17 mammal species, 39 bird species, and 32 herpetofauna species (17 amphibian species and 15 reptile species) within the concession. The study area is inhabited by at least 5 nationally protected species, 8 threatened species according to the IUCN Red List, and 10 species listed in the CITES Appendices. Besai Hydropower Plant concession has the potential to act as a refugium from the threat of land cover change, particularly conversion to plantations, which is a common occurrence around the study area.